Anti-Corrosion Activity of Ephedrine on Mild Steel in Acidic Medium - Al-Baghdadi, Shaimaa Basim Khalaf (Al-Nahrain Journal of Science, 2017)
Anti-corrosion activity of ephedrine "2-(methylamino)-1-phenylpropan-1-ol" was investigated by Gravimetric strategy and completed with mellow steel samples in 1M HCl as corrosive solution at different temperatures. The target compound displayed greatest efficiency of 84% at 500mg/L. The outcomes of weight loss method revealed that the target compound represents a one of the best inhibitors for mild steel and these efficiencies expanded with expansion in the concentrations of the ephedrine. SEM (Scanning Electron Microscopy) was utilized examine the steel surface at the most noteworthy erosion hindrance investigated concentration.